TINGKAT EFEKTIVITAS PENYULUHAN PERTANIAN Di KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Kardiana K; Abdul Mutolib; Helvi Yanvika; Indah Listiana; Indah Nurmayasari (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Improving the performance of agricultural extension workers will determine the future of agricultural development which is basically to increase the income of the agricultural sector. The purpose of this study was to analyze the effectiveness of agricultural extension in Jati Agung Subdistrict, South Lampung Regency, analyze the performance of agricultural extension workers, determine the level of participation of farmers in agricultural extension, determine the level of farmer satisfaction with the performance of agricultural extension workers. The study was conducted in the Village Building District of Jati Agung, South Lampung Regency. The data used in this study are primary data. The results showed that the agricultural instructor in Desa Fajar Baru had performed well, the delivery of material by the instructor was carried out well so that the farmer easily understood all the material easily, the farmer was satisfied with the extension agent's visit because the extension worker was always actively visiting farmers every month. The effectiveness level of counseling in Fajar Baru Village, Jati Agung Subdistrict is in the criteria of Not Effective. The instructor's performance is assessed from the instructor's aspect as a facilitator and the counseling material is considered to be quite good and satisfactory. Agung is still low, and the performance of agricultural counseling in Fajar Baru Village, Jati Agung Sub-district is satisfactory with a satisfaction range of 1.91 to 2.25.